Influencia de los servicios web en la reutilización de código en el desarrollo de software - Pérez Otiniano, Jhonatan Jhossep (2013)
The present research aims to show the influence of web services in code reuse and software development, four specific objectives were proposed in which determines initial assessment of the applications that use services web, web service developed with the programming language C # and integrates software applications existing, determines the degree of reuse of software applications using web services and finally evaluates applications after using web services._x000D_ To achieve these objectives, we proceeded to determine the population that is 50 applications developed in company Grupo Privado del Norte S.A.C & LatinTechnologies, obtaining a sample through random sampling of 20 applications._x000D_ The method of the research are: empirical, descriptive - explanatory and analytic-synthetic, posing as contrasting design hypothesis statistical test T -Student contrasting with contrasting method Pretest - posttest ._x000D_ Finally and determine the degree of code reuse through the maintenance rate applications , which shows an increase in applications to the web service by 1.7 points on average facilitating code maintenance